Exploring Horizontally Flipped Interaction in Virtual Reality for Improving Spatial Ability - Bozgeyikli, Lal Lila; Bozgeyikli, Evren; Schnell, Christopher; Clark, Jaclynn (IEEE transactions on visualization and computer graphics, 2023)
Virtual reality (VR) is a high-fidelity medium that can offer experiences that are close to real-life. Spatial ability plays an important role in human life, including academic achievement and advancement in work settings. Spatial ability is known to be improved by practicing relevant tasks. Mental rotation and spatial perception are among such tasks that improve spatial skills. In this research, we investigated a "mirror-reversed" interaction technique in a cup stacking task in VR and looked into its effects on spatial ability, brain activity regarding spatial processing and attention (measured with EEG), performance, and user experience in male participants. Participants stacked cups according to given patterns using direct manipulation with horizontally flipped controls, similar to looking in a mirror while performing object manipulation in real life. In a between-subjects user study, we compared this novel interaction with a baseline where the participants completed the same task with regular controls. Although there was no significant main effect of group on the mental rotation and perspective taking/spatial orientation tests scores, within-group analysis indicated a trend toward an improvement in the mirror-reversed group in spatial orientation, while both groups showed a trend toward improvement in mental rotation. Participants in both groups got better at the task over time (their task completion durations decreased). EEG data revealed significant theta band power increase in the mirror-reversed group whereas there was no difference in the alpha band power between the two groups. Our results are encouraging for exploring spatially challenging interactions in VR for spatial skills training. We share the implementation and user study results, and discuss the implications.